Divergent priorities in flood adaptation - Jennifer Niemann-Morris; A R Siders; Miyuki Hino; Caroline M Kraan; Armen Agopian; Christopher Samoray; Katharine J Mach (Environmental Research: Climate)
Actions to reduce flood risk often appear to run counter to other societal goals, and resolving these conflicts is important as flood adaptations increasingly transform settlements and societies. Here, we evaluate the tensions between flood risk reduction and other priorities in the context of voluntary buyouts of flood-prone properties in the United States—a controversial flood response to restore land to open space, but with trade-offs. We apply a nation-wide systematic review (133 literature references, 1983–2023) to assess goals stated for buyouts and combine it with a comprehensive media analysis (281 media articles, 1993–2023) to compare those goals to the experiences and results perceived by buyout implementers, residents, and other practitioner groups. Across the systematic-review literature, flood risk reduction dominates goals expressed for buyouts (62.6% of documented goals), and local government predominates in this goal setting (61.7% of documented goals). However, involved and affected actors—especially residents—perceive outcomes beyond flood risk reduction, most notably in the experiences of buyout implementation itself (35.5% of documented resident perceptions) and in results impacting social and economic priorities (49.5%). Despite the difficulties of buyouts, the systematic-review literature largely reflects positive perceived outcomes (79.4% of outcome sentiments, weighing each buyout location equally), but nonprofit organizations and residents perceive largely negative outcomes. Media coverage related to buyouts is more negative than positive but with improved sentiments through time. Our findings point to the importance of designing, implementing, and evaluating flood adaptations not just as flood control measures given their consequences for other societal objectives. The uneven documentation on buyouts also implies opportunities to learn from contexts where buyouts have been integrated into everyday life with little fanfare, through mechanisms either novel or perhaps routine, yielding insights into making ambitious climate adaptations a common, more ordinary, and increasingly imperative occurrence.